Characterization and acid resistance test of one-part geopolymer from fly ash and water treatment sludge - Orbecido, Aileen H. (Animo Repository, 2018)
Development of geopolymers from wastes or by-products introduces a sustainable approach to replace ordinary Portland cement (OPC)-based concrete with an eco-material of lower green-house gases emissions. However, safety concerns related to the conventional two-part geopolymer has limited large-scale applications of the product. In this context, a novel one-part geopolymer from coal fly ash and water treatment sludge has been presented. The transformation of raw materials to geopolymer was observed by FTIR, SEM and XRD analyses. Acid resistance test has proved that the new binder had great durability against sulphuric acid attack. After 28 days immersion in 5% H2SO4 solution, weight of all samples was hardly changed. Compressive strength, on the other hand, has not decreased but significantly increased as curing time increased. The properties were also compared to those of control samples cured in water. It was demonstrated that strong acid immersion did not create any noticeable effect on the weight and strength of one-part geopolymer system developed from coal fly ash and water treatment sludge. © The Authors, published by EDP Sciences, 2018.